2002
DOI: 10.1515/arh-2002-0008
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Interpretation of the Slump Test

Abstract: We examine the validity of the slump test for predicting the yield stress of polymeric suspensions and mineral suspensions. First we propose a modification of this test: in order to make measurements on fluids with high yield stress (of the order of several hundreds of Pascal) we add a mass at the sample top. From detailed observations of the slump in time we show that, for polymeric suspensions (hair gel and sewage sludges), two critical stresses can be distinguished which almost exactly correspond to the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…This phenomenon is almost negligible in highly concentrated mixtures but predominantly observed in less concentrated mixtures. From Baudez et al (2002), it is known that the plane surface roughness does not influence the slump height S of the unyielded central part. However, the influence of roughness on the profile of deposit has not been investigated yet.…”
Section: Rheometrymentioning
confidence: 99%
“…This phenomenon is almost negligible in highly concentrated mixtures but predominantly observed in less concentrated mixtures. From Baudez et al (2002), it is known that the plane surface roughness does not influence the slump height S of the unyielded central part. However, the influence of roughness on the profile of deposit has not been investigated yet.…”
Section: Rheometrymentioning
confidence: 99%
“…We mainly used a commercial hair gel (Yplon S.A., Belgium), basically made of water and Carbopol, with the internal structure of a physical gel of density close to that of water. Previous studies showed that this material exhibits the rheological behavior of a typical yield stress fluid with a flow curve, which may well be represented by a Herschel-Bulkley model (Baudez et al 2002). Here the yield stress, as determined from a series of creep tests at different levels with a parallel plate rheometer (see Baudez et al 2002), was found to be 70 Pa. To change the yield stress value we also used suspensions of Carbopol ® 940 (ACROS Organics, France) at different solid fractions, prepared according to the procedure described in Curran et al (2002).…”
Section: Experimental Setup and Proceduresmentioning
confidence: 93%
“…A comparison of these theoretical predictions with experimental results was rather successful, even if there remained a significant uncertainty on the exact determination of the yield stress. A comprehensive comparison between rheometric measurements and slump test results has appeared elsewhere (Baudez et al, 2002).…”
Section: Practical Determination Of the Yield Stress With The Slump Testmentioning
confidence: 99%
“…Since in general pasty sewage sludge have higher yield stresses than fresh concrete, we proposed a modification of the slump test (Baudez et al, 2002), i.e. an additional mass is placed at the top of the sample, which assures that small sample volumes can still be used (Fig.…”
Section: Practical Determination Of the Yield Stress With The Slump Testmentioning
confidence: 99%
See 1 more Smart Citation